1989
DOI: 10.1209/0295-5075/10/6/005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies of Small Three-Dimensional Gold Clusters on Graphite by Scanning Tunnelling Microscopy

Abstract: Three-dimensional gold clusters deposited in UHV on clean natural graphite are imaged at the atomic level using scanning tunnelling microscopy (STM). After STM observation, the samples are characterized by transmission electron microscopy (TEM). The smallest observed gold clusters (1.0 to 1.5 nm) are close-packed, two atomic layers high, and stable over a period of time of at least 5 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…in figure 5(d), which is due to the large average cluster size of more than 5 nm. As has been shown before for supports with a threefold symmetry axis, the clusters grow in the (111) epitaxy and have a threedimensional tetrahedral shape [8,36], which they keep up to sizes of a few nanometres [2]. Clusters with larger sizes than 5 nm exhibit different equilibrium shapes, namely truncated tetrahedrons [2], as shown by TEM and STM [36][37][38].…”
Section: S133mentioning
confidence: 84%
“…in figure 5(d), which is due to the large average cluster size of more than 5 nm. As has been shown before for supports with a threefold symmetry axis, the clusters grow in the (111) epitaxy and have a threedimensional tetrahedral shape [8,36], which they keep up to sizes of a few nanometres [2]. Clusters with larger sizes than 5 nm exhibit different equilibrium shapes, namely truncated tetrahedrons [2], as shown by TEM and STM [36][37][38].…”
Section: S133mentioning
confidence: 84%
“…15 The most recent results suggest that primarily the low-coordinated atoms are bonding sites for CO and O 2 , 9,[16][17][18][19] and that the interaction with the substrate 14,20 or charge transfer could also play a role in the catalysis by gold clusters. 12,13 Scanning probe microscopy offers an excellent possibility for in situ studies of the properties of nanoclusters, and scanning tunneling microscopy ͑STM͒ has been applied to several model systems, [21][22][23][24][25][26] but the requirement of a conducting sample has restricted the STM's access to the important class of insulating surfaces. In principle dynamic scanning force microscopy ͑dynamic SFM͒ [27][28][29] offers the capability of imaging both the adsorbed metal clusters and the insulating surface in atomic resolution, hence providing unprecedented information about the cluster structural properties.…”
Section: Introductionmentioning
confidence: 99%
“…So studies of clusters on surfaces have great physical and technical importance. Some experiments [8,9] have shown that the surface may play an important role in determining the structure and the stability of clusters. In a recent experiment [10] involving Au and Ag clusters supported on a tungsten tip, the melting point of the clusters was found to be a constant value when the diameter of the clusters was less than 2 nm; some authors [11] have suggested that this may be attributed to the strong interaction between the clusters and the surfaces.…”
Section: Introductionmentioning
confidence: 99%